THE STUDENTS AND TEACHER’S VIEWS ON THE USE OF E-TEXTBOOKS IN READING CLASSROOM - Hera Nopiyanti; Abdul Asib; Sri Samiati Tarjana (Universitas Sembilanbelas November Kolaka, 2019)
Since the development of information technology grows rapidly, the educational institutions are offered various media or tools of instruction supporting and enhancing teaching and learning process. E-textbooks are a variety of technology which changes the experience of classroom language from traditional into paperless in reading classroom. This technology facilitates the teacher and the students to utilize computer and paper-based reading tasks in realizing the functions of the e-learning environment. It creates an atmosphere of independent acquisition and quality pedagogical strategies which can improve the efficiency of teaching and learning. The use of electronic textbook completed by hypertext and multimedia tools clearly demonstrated the advantage of this technology compared with traditional textbooks. This research is about the teacher and students’ views on using e-textbooks for reading in EFL classroom. This research aims to identify, describe, and analyze teacher and students’ perceptions on using e-textbooks technology as the paper textbooks in teaching and learning reading for Indonesian lower secondary school. Mix method of qualitative and quantitative was applied in the research. The research was conducted on an English teacher and the twenty-five eighth-grade students who used e-textbooks in reading classroom of Islamic junior high school in Lampung, Indonesian. The techniques of data collection used were interviews, questionnaires, observation, and documentation. The results showed that the teacher and majority of the students had a good perception of using e-textbooks. Considering insufficiently available textbooks provided by the government which do not meet students’ need and interest, the teacher should find out and develop many other resources for teaching and learning in the classroom. However, e-textbook technology will not displace traditional paper textbooks in the future, but they will become the perfect complement to paper textbooks.